Kinetic and thermodynamic study of the interactions between human carbonic anhydrase variants and polystyrene nanoparticles of different size. Issue 42 (12th April 2016) - Assarsson, A.; Nasir, I.; Lundqvist, M.; Cabaleiro-Lago, C.
Abstract : The protein packing at the surface may increase as the size of particles decreases given the right particle–protein characteristics. Abstract : The activity and adsorption of three variants of human carbonic anhydrase (HCA) with similar topology but variation in charge and stability were studied in the presence of carboxyl-modified polystyrene nanoparticles of different sizes ranging from 25 nm to 114 nm. The balance of forces driving the adsorption of carbonic anhydrase variants is affected by the physicochemical properties of the protein and the nanoparticle size. All enzymes are totally inhibited upon adsorption due to the transition towards a molten globule like state that lacks enzymatic activity. The size of the particle affects the adsorption of human carbonic anhydrase I and N-terminal truncated human carbonic anhydrase II. Investigations on pH effects indicate that the size of the particle modulates the lateral interactions at the protein layer for these particular variants whose adsorption is mainly driven by electrostatic forces. A third variant, human carbonic anhydrase II, instead shows no strong influence of nanoparticle size which supports an adsorption process mainly driven by the hydrophobic effect.